2020
DOI: 10.1016/j.heliyon.2020.e04804
|View full text |Cite
|
Sign up to set email alerts
|

Using Twitter for crisis communications in a natural disaster: Hurricane Harvey

Abstract: This article examines the use of social media, specifically Twitter, in crisis communications during a natural disaster and how it can provide information, guidance, reassurance and hope to victims while keeping others across the nation and the world apprised of the situation so they can provide assistance, as needed. A case study looks at how the mayor of Houston, Texas, Sylvester Turner, used Twitter during Hurricane Harvey in August and September of 2017. The case study is analyzed using restorative rhetori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Social media can thus be used not only as a complementary channel to release crisis information, but also a tool to monitor public opinions, promote social cohesion, and foster support ( Alexander, 2014 , Zhang et al, 2019 ). It was found that during crises such as extreme weather and outbreaks of infections, crisis-related messages communicated by news media outlets, government and health authorities on social media could increase public engagement as they prompted public responses in form of ‘likes’, ‘shares’, and ‘comments’ (e.g., Ngai et al, 2020 , Bruns et al, 2012 , Criado et al, 2020 , Househ, 2016 , Vera-Burgos and Padgett, 2020 ). These social media cues are meaningful indicators of engagement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social media can thus be used not only as a complementary channel to release crisis information, but also a tool to monitor public opinions, promote social cohesion, and foster support ( Alexander, 2014 , Zhang et al, 2019 ). It was found that during crises such as extreme weather and outbreaks of infections, crisis-related messages communicated by news media outlets, government and health authorities on social media could increase public engagement as they prompted public responses in form of ‘likes’, ‘shares’, and ‘comments’ (e.g., Ngai et al, 2020 , Bruns et al, 2012 , Criado et al, 2020 , Househ, 2016 , Vera-Burgos and Padgett, 2020 ). These social media cues are meaningful indicators of engagement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a case study, Catherine et al investigate the usage analysis of the Twitter handle of the Mayor of Houston during the hurricanes Sandy and Harvey in August and September of 2017 [29]. In another study, researchers compared machine learning algorithms in the extraction of geo-tagged tweets during emergencies; they used 10 machine learning classifiers on location-oriented disaster-related tweets [30].…”
Section: Twitter During Natural Disastersmentioning
confidence: 99%
“…During multiple natural disasters, social media has been used to coordinate volunteer efforts, relay real-time information, aid in the localization of victims, and access to resources such as food. [28][29][30][31][32] Despite this, communication remains one of the greatest challenges during a large-scale disaster. 27 28 33 During the Maryville shooting, it took 28 minutes to get communication to law enforcement.…”
Section: #Disaster Preparedness: the Role Of Social Media In Disasters And Mass Casualty Eventsmentioning
confidence: 99%